Reconstruction of Women’s Image in the Novel Innahu ad-Dam by Nawal El Saadawi - Muasomah; Dzulkifli M. Mooduto (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This study aims to determine the reconstruction of the image of women in the novel Innahu ad-Dam by Nawal El Saadawi who is a militant feminist figure in Egypt. This novel tells of the courage of the female characters in the big demonstration that took place in Tahrir Square, Egypt. The theory used in this research is Jonathan Culler’s theory of literary criticism with the concept of ‘reading as a woman.’ The research method used is descriptive analysis method with consideration of the objects studied are novel texts. The formal object of this research is the reconstruction of the image of women, while the object of this research is the novel Innahu ad-Dam by Nawal El Saadawi. The result of this research is the reconstruction of the image of women described by Nawal El Saadawi. Women who are constructed by socio-culture as weak creatures, in the view of the image of traditional women, in this study the results obtained that the female characters depicted have the image of independent women.